Laparoscopic distal gastrectomy for gastric cancer in a patient with situs inversus: a case report - Kei Sato; Junki Yamada; Naohito Meguro; Hiroshi Onishi; Kanechika Den; Hiroyuki Baba; Mitsutaka Sugita (Surgical Case Reports)
Abstract Background Situs inversus (SI) is a rare congenital condition characterized by organ transposition from their normal positions. Careful preoperative planning is important for the safe operation of patients with SI because only a few surgeons have operated on such patients. Here, we report the case of a patient with SI who underwent laparoscopic distal gastrectomy (LDG) with D2 lymph node dissection (LND) for advanced gastric cancer (GC). Case presentation The patient was a 72-year-old man diagnosed with GC. Upper endoscopy revealed a type 3 tumor in the anterior wall of the stomach body. Multidetector computed tomography showed no obvious GC metastasis or inverted organs. The preoperative diagnosis was cStage IIB (i.e., cT3, cN0, and cM0) GC with SI. Although liver retracting and intracorporeal suturing required special attention, LDG with D2 LND and Billroth-I reconstruction were safely performed by reversing the usual procedure. The patient was discharged 10 days after the surgery. Conclusions To safely perform laparoscopic surgery for GC in patients with SI, sufficient preoperative preparation is necessary. In particular, a reversible method of liver retraction should be prepared.